PALI DALAM AKTIVITAS SEHARI-HARI SUKU DAYAK NGAJU DESA MANTANGAI HULU KABUPATEN KAPUAS (Pali in the Daily Activities of Dayak Ngaju Village of Exgai Hulu Kapuas Regency) - Lastaria Lastaria; Lailatul Fithriyah Azzakiyah (Balai Bahasa Sulawesi Selatan, 2022)
Dayak Ngaju tribe is a tribe rich in ancestral heritage so that it has a culture that is quite adhered to by the owner of the culture itself. However, the culture is only inherited from oral to oral so that the form of cultural writing of the Dayak Ngaju community is very minimal. Pali or pamali is also included in the oral tradition of Dayak Ngaju which is almost extinct due to the development of the times. However, if you investigate further that behindthe word